DOERTE WEIG - Tensional Responsiveness. Ecosomatic Aliveness and Sensitivity with Human and More-than - Gálvez, María Auxiliadora (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2025)
DOERTE WEIG Tensional Responsiveness. Ecosomatic Aliveness and Sensitivity with Human and More-than. Transcript Verlag, Germany, 2021, 202 pp. Paperback. 38.00 € Desde febrero de 2024, acceso abierto: https://www.transcript-publishing.com/978-3-8376-6011-1/tensional-responsiveness/?number=978-3-8394-6011-5&c=310000025 Idioma: inglés ISBN: 978-3-8376-6011-1 / ISBN: 978-3-8394-6011-5